Inulin extraction from Jerusalem artichoke (Helianthus tuberosus L.) tuber powder and its application to yoghurt snack - Khuenpet, K.; Truong, N. D. P.; Polpued, R. (International Journal of Agricultural Technology, 2020)
A ratio of Jerusalem artichoke tuber powder (JATP) and water at 1:20 (w/w), the concentrated Jerusalem artichoke extract contained the highest inulin content of 33.14 mg/ml and 2.06 mg/ml of reducing sugar. For yoghurt mixture formulation, the concentrated JA extract was used as an ingredient. Yoghurt was mixed with sugar, concentrated JA extract and juice, namely tomato juice 20% (T), lemon juice 20% (L), passion fruit juice 20% (P), the combination of T 10% with L 10% (TL), T 10% with P 10% (TP) or L 10% with P 10% (LP). The sensorial evaluation demonstrated that the treatment added with P 20% got significantly higher scores than other treatments (p<0.05), which were between 7.03 to 7.93 in aspects of color, flavor, sweetness, sourness and overall acceptability indicating that the panelists like sample very much. The sugar in P-JA yoghurt mixture formula was substituted by four sweeteners including maltitol, xylitol, prebiotic syrup and JA syrup. It appeared that the sugar substitution with JA syrup in P-JA yoghurt mixture caused insignificantly different in flavor, sweetness, sourness and overall acceptability from control (sugar). Yoghurt fortified with concentrated JA inulin, PJ and JA syrup was foamed and dried by foam-mat drying technique. The addition of 35% foaming agent solution (2% methocel and 1.5% carboxymelthyl cellulose) produced stable foam. The obtained foam was squeezed into circle shape and dried at 70oC for 2 h to form JA inulin yoghurt snack. The moisture content, aw and pH of dried snack were 5.73%wb, 0.39 and 4.24 respectively. JA yoghurt snack contained inulin 129.78 mg/g and reducing sugar 146.44 mg/g.